Renal Chronic Disease And Management Of It`S Complications - Marsida Duli; Qamil Dika; Matilda Bushati (European Scientific Journal, ESJ, 2016)
Chronic kidney disease is recognized as a major health problem. Numbers of prevalent SRK patients will continue to rise, reflecting the growing elderly population and increasing numbers of patients with diabetes and hypertension. As numbers of SRK patients increase, primary care practitioners will be confronted with management of the complex medical problems unique to patients with chronic renal impairment. As well documented in the literature, the nephrologist rarely manages the medical needs of SRK patients until renal replacement therapy is required. The most frequent complications associated with SRK: anemia, hyperlipidemia, nutrition, osteodystrophy, and cardiovascular risk. Patients with SRK present several complex management issues to health care providers. The staging system introduced by the National Kidney Foundation is a significant accomplishment, which stratifies patients according to disease severity. In addition, the guidelines are an excellent tool for management of SRK and dialysis patients and recommend treatments according to disease stage. These interventions may reduce morbidity and mortality in these patients. With early identification and treatment of anemia, renal osteodystrophy, uremia, hyperlipidemia, and cardiovascular disease, primary care physicians and nephrologists together are making significant strides toward extending and improving the lives of patients with chronic renal disease.